THE ROLE OF ENGLISH IN MARKETING SUSTAINABLE GASTRONOMY FOR Internasional TOURISTS - Achmadi, Nila Sartika; Murtopo, Ali; Wibowo, Yusep Windhu Ari; Nainggolan, Kristina Novalina (International Journal of Entrepreneurship and Tourism, 2025)
This study investigates the pivotal role of English in marketing sustainable local gastronomy to international tourists. Employing a qualitative descriptive approach through a comprehensive literature review, the research systematically synthesizes existing knowledge to formulate effective marketing strategies. Findings reveal four key strategies: strategic English branding and menu localization, enhanced English communication for tourist comfort and safety, digital and international English-centric promotion, and robust capacity building and training in English for sustainable gastronomy. These strategies are crucial for overcoming communication barriers, improving tourist experiences, and boosting global competitiveness. The study concludes that leveraging English is indispensable for articulating the unique value of sustainable local gastronomy, fostering cross-cultural understanding, and contributing to its long-term viability and economic prosperity on the international stage.